Murine Abdominal Aortic Aneurysm Intraluminal Thrombus Composition and Structure - Cortland H. Johns; Luke E. Schepers; Annabelle M. F. Foist; Ethan P. Foster; Anish Bedi; Niharika Narra; Claudia K. Albrecht; Abigail D. Cox; Craig J. Goergen (Annals of Biomedical Engineering, 2026)
Purpose Many abdominal aortic aneurysm (AAA) patients develop intraluminal thrombus (ILT), but the role of ILT in AAA progression and rupture is poorly understood. Methods To evaluate ILT in AAAs, we induced AAAs in C57Bl6/J mice via surgical application of topical elastase to the abdominal aorta below the renal arteries and administration of β-aminopropionitrile (BAPN) in drinking water. Ultrasound images of these AAAs were collected longitudinally over a period of 56 days to evaluate AAA growth over time. We semi-quantitatively assessed elastin degradation and inflammation from Movat’s pentachrome and H&E-stained samples, respectively. Additionally, we assessed extracellular matrix composition and elastin quality through Movat’s pentachrome stained samples. Results Mice subjected to elastase + BAPN exhibited continuous and significant AAA growth over time. Mice with ILT had more significant expansion over the length of the study ( p Conclusion Understanding the relationship between ILT formation, aortic wall degradation, and inflammation could help refine clinical strategies for monitoring and treating AAAs. These data suggest that work focused on modulating inflammation and ILT formation could offer promising pathways for non-surgical intervention in AAA treatment.

Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Relaxed Neighbor Joining: A Fast Distance-Based Phylogenetic Tree Construction Method - Jason Evans; Luke Sheneman; James Foster (Journal of Molecular Evolution, 2006)

A critical analysis of reasons for improved survival from invasive cutaneous melanoma - Colin Glen Luke; Brendon John Coventry; Erwin Joseph Foster-Smith; David Murray Roder (Cancer Causes & Control, 2003)